Anthropometric characteristics of young turkish male athletes - Pelin, C.; Kürkcüoglu, A.; Özener, B.; Yazycy, A. C. (Collegium Antropologicum, 2009)
Comparative reports on the anthropometric characteristics of athletes are certainly important in modern sports and have long been studied by sports scientists. Studies on Turkish athletes however, are limited. In the present study physical characteristics of athletes active in various sports (American football, basketball, volleyball and football) were observed and compared to each other and to those of non-athlete individuals. 153 volunteer male subjects participated in the study. All of the athletes were licensed members of teams in inter-university leagues. All subjects were given information about the objectives of the study and were advised of the manner with which the anthropometric measurements would be obtained. In addition to 17 anthropometric values, body mass index (BMI) and somatotype components were calculated and evaluated. Length, breadth, and girth values were evaluated by ANCOVA and height and weight were used as co-variate factors. The other variables were evaluated by metric and non-metric ANOVA. The results of the study indicate that basketball and volleyball players were characteristic with their longer lower limb length; American football players were with their wider biiliac breadth and higher girth values; and football players with their small structure. It was also observed that Turkish athletes have higher endomorphy and lower mesomorphy values when compared to athletes from other countries.